2011
DOI: 10.1093/jac/dkr355
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 7-amino-4-methylcoumarin as an effective antitubercular agent: structure–activity relationships

Abstract: The present study clearly demonstrated the in vitro antitubercular potential of the novel drug candidate NA5. Further studies are warranted to establish the in vivo efficacy and therapeutic potential of NA5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…Similar observations were previously reported for M . tuberculosis that was treated with isoniazid or other compounds that target mycolic acids 26, 27 . These effects of IMB-YH-8 on cell wall and cell morphology are in agreement with the function of its target PknB in controlling cell shape and regulating cell wall synthesis that requires mycolic acids 6, 28, 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations were previously reported for M . tuberculosis that was treated with isoniazid or other compounds that target mycolic acids 26, 27 . These effects of IMB-YH-8 on cell wall and cell morphology are in agreement with the function of its target PknB in controlling cell shape and regulating cell wall synthesis that requires mycolic acids 6, 28, 29 .…”
Section: Discussionmentioning
confidence: 99%
“…YX-28 isolated from Ginkgo biloba L. may be used as natural preservative in food (Liu et al 2008). AMC also exhibited maximum antitubercular activity, with MIC of 1 mg L −1 against M. tuberculosis when produced by synthetic pathway (Tandon et al 2011).…”
Section: Ascomycetes Fungimentioning
confidence: 99%
“…In addition, the current anti-tuberculosis drugs induce various/serious side effects including hepatotoxicity, ototoxicity, and nephrotoxicity. In this aspect, as one of feasible alternatives for overcoming limitations of the drug's side effects, particularly, including rifampicin, isoniazid, ethambutol and moxifloxacin, various studies for developing anti-tuberculosis drugs were reported from active substances derived from traditional diverse medicinal plants and biological resources [19][20][21][22][23]. However, antituberculosis agents of effective/safe next-generation that can be utilized or used as potential/novel first-line anti-tuberculosis drugs, particularly, the extracts, natural products, and/or semi-synthetic compounds, have not yet been reported in the global pharmaceutical market.…”
Section: Discussionmentioning
confidence: 99%